The linear equation y = -6x + 2; -12x - 2y = -4 has no solution
<h3>Linear equation</h3>
y = -6x + 2
-12x - 2y = -4
- Substitute y = -6x + 2 into (2)
-12x - 2y = -4
-12x - 2(-6x + 2) = -4
-12x + 12x -4 = -4
-12x + 12x = - 4 + 4
0 = 0
y = -6x + 2
y - 2 = -6x
x = (y - 2) / -6
-12x - 2y = -4
-12(y- 2)/ 6 - 2y = -4
(-12y + 24) / 6 - 2y = -4
-2y + 4 - 2y = 4
0 = 0
Learn more about linear equation:
brainly.com/question/4074386
#SPJ1
When we divide a number and if it does not get divided completely, we are left with a remainder. Let us understand this with the help of an example. The quotient can be calculated by dividing the dividend with the divisor. Quotient = Dividend ÷ Divisor. The answer is 20.63
Answer:
there are 3 answers
Step-by-step explanation:
the original is 23 1/2
Now he can do 23
or he can do 22
A for a box, the surface area is given by:
6l², where l is the length of one side.
If the side is increased 10 times,
6(10l)²
=100 x6l²
The surface area increases 100 times. Thus, the new surface area is
272 * 100
= 27,200 sq in
Answer:
1. y= 2/5x+11
2. y=3x-15
2y-5x=9
Step-by-step explanation:
I did this already